Feasibility study on generation and storage of power generated by mechanical footstep power generator - Basnet, Shirish; Ranabhat, Kushal; Shrestha, Min Narayan (Journal of Engineering and Sciences, 2023)
With the increasing demand for electrical energy in today’s world, science has discovered many new concepts and methods for energy production. Among those concepts, a mechanical footstep power generator converts mechanical energy to electrical energy. The ultimate purpose of this research is to fabricate the footstep power generator and to produce electrical energy. The project is based on a Rack and Pinion mechanism to convert mechanical energy into electrical energy by utilizing energy during walking. The maximum voltage and current output of 8.22 Volt and 0.12 Ampere were obtained when the maximum load of 70 kg was applied to the system. This research has shown that mechanical footstep power generators have great potential for powering small electrical devices in various public places.